A novel noninvasive surface ECG analysis using interlead QRS dispersion in arrhythmogenic right ventricular cardiomyopathy. - Wan-Hsin Hsieh; Chin-Yu Lin; Abigail Louise D Te; Men-Tzung Lo; Cheng-I Wu; Fa-Po Chung; Yi-Chung Chang; Shih-Lin Chang; Chen Lin; Li-Wei Lo; Yu-Feng Hu; Jo-Nan Liao; et al. (PLoS ONE)
Background This study investigated the feasibility of using the precordial surface ECG lead interlead QRS dispersion (IQRSD) in the identification of abnormal ventricular substrate in arrhythmogenic right ventricular cardiomyopathy (ARVC). Methods Seventy-one consecutive patients were enrolled and reclassified into 4 groups: definite ARVC with epicardial ablation (Group 1), ARVC with ventricular tachycardia (VT, Group 2), idiopathic right ventricular outflow tract VT without ARVC (Group 3), and controls without VT (Group 4). IQRSD was quantified by the angular difference between the reconstruction vectors obtained from the QRS-loop decomposition, based on a principal component analysis (PCA). Electroanatomic mapping and simulated ECGs were used to investigate the relationship between QRS dispersion and abnormal substrate. Results The percentage of the QRS loop area in the Group 1-2 was smaller than the controls (P = 0.01). The IQRSD between V1-V2 could differentiate all VTs from control (P<0.01). Group 1-2 had a greater IQRSD than the Group 3-4 (V4-V5,P = 0.001), and Group 1 had a greater IQRSD than Group 3-4 (V6-Lead I, P<0.001). Both real and simulated data had a positive correlation between the maximal IQRSD (γ = 0.62) and the extent of corresponding abnormal substrate (γ = 0.71, both P<0.001). Conclusions The IQRSD of the surface ECG precordial leads successfully differentiated ARVC from controls, and could be used as a noninvasive marker to identify the abnormal substrate and the status of ARVC patients who can benefit from epicardial ablation.